Simulation of Dispersion of Air Pollutants and Acidic Precipitation - Choong, Wei Yee (1999)
Acidic precipitation poses a threat to ecosystems. Many countries in Europe and northeastern parts of the United States of America have experienced forest decline in their mountainous region due to acidic deposition. Malaysia, being a rapidly industrialised nation, succumbed to acidic precipitation too. This study sought to determine the trend of acidic precipitation in Malaysia, particularly in hilly terrain, and to investigate the significance of building an incinerator near a hill. Wet fallout data for 1996 for three hilly sites were collected. These data were analysed statistically and compared to the data of low-lying areas nearest to the hill sites, and also to a polluted area. Numerical simulations on the dispersion of plume from an incinerator were carried out using a commercial software FLUENT to determine the flow pattern of the plume and its effect on the hill. Simulations were carried out for two scenarios that were for an incinerator located in an open area, and the other located near to a hill. Results of this study indicated that the studied hill sites received acidic precipitation at an average of 40% for 1996, with an average annual pH of 5.0. This reflected that the tropical forest in these hilly sites has a high potential risk of exposure to acidic precipitation which could be detrimental to them. Results from the simulation showed that the plume emitted by the incinerator has the most significant impact on the leeward side of the hill, whereby the calculated pH of rainwater here was typically around 2. In the case of an open area, the pH of the rainwater was typically around 3 - 4. The calculated pH of the fog/cloud water was found to be two to three order more acidic compared to rainwater. This indicated that the forest in a highland area, which is usually surrounded by high moisture content in the atmosphere, may receive high acidic deposition due to its contact with the fog/cloud. However, the sulphate deposition flux calculated in this study was well below the allowed load of20 kg/ha.yr.